Assessing Lean adoption in food SMEs: Evidence from Greece. Issue 1 (2nd January 2018) - Psomas, Evangelos; Antony, Jiju; Bouranta, Nancy
Abstract : Purpose: The purpose of this paper is to determine the current state of the Lean principles adopted by food small and medium-sized enterprises (SMEs). Design/methodology/approach: The case study approach was undertaken in order to gain insights into Lean adoption. Nine Greek food SMEs certified according to the ISO 9001 quality management system (QMS) and the ISO 22000 food safety management system (FSMS) were approached. Interviews were conducted with the chief executive officers and the company managers in charge of the QMS or FSMS, based on a structured questionnaire. Findings: The food SMEs participating in the present study adopt Lean principles to a high extent. However, there is room for further improvement. Research limitations/implications: The fact that the data collected suggests subjective business evidence and not objective as well as the fact that only two representatives of each of the nine food SMEs were conducted, comprise the main limitations of the present study. So, the results should be considered with caution, as far as the Lean adoption in the Greek food sector is concerned. Based on these limitations, future research suggestions can be made. Practical implications: Based on the present study, suggestions can be made regarding the successful adoption of Lean principles, not only for the sample SMEs but also for the whole of the food sector. More specifically, by determining the strengths and weaknesses of the food SMEs' efforts to adopt Lean, suitable managerial initiatives can be undertaken by these companies as well as the whole sector to fully adopt Lean and derive the respective benefits. Originality/value: The paper provides insights into the adoption of Lean principles in the Greek food sector. This is the first study in the field of Lean that has been carried out in the Greek food SMEs.